2008
DOI: 10.1210/jc.2007-2707
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Gene CAG Repeat Polymorphism and X-Chromosome Inactivation in Children with Premature Adrenarche

Abstract: Context: There is variation in the adrenal androgen levels and clinical findings of children with premature adrenarche (PA). Objectives:We hypothesized that androgen sensitivity, indicated by the length of CAG repeat in the X-chromosomal androgen receptor (AR) gene has a role in the polygenic pathogenesis of PA. Design and Patients:We performed a cross-sectional association study among 73 Finnish Caucasian children with PA (10 boys and 63 girls) and 97 age-and gender-matched healthy controls (18 boys and 79 gi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
30
0
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 38 publications
2
30
0
3
Order By: Relevance
“…In addition, an ACTH receptor polymorphism has been found to be associated with the severity of PA also indicating a modulatory effect of the hypothalamic-pituitary-adrenal (HPA) axis in this condition (37). In the same cohort, Lappalainen et al (38) could also show that mean CAG repeat length of the androgen receptor (AR) gene is shorter in PA girls and that a polymorphic allele of the transcription factor TCF7L2, involved in the Wnt signalling pathway, was more frequent in PA subjects (39). However, genomewide association studies in appropriately powered cohorts of children with early androgen excess are currently lacking.…”
Section: Adrenarche Pubarche and Pubertymentioning
confidence: 86%
“…In addition, an ACTH receptor polymorphism has been found to be associated with the severity of PA also indicating a modulatory effect of the hypothalamic-pituitary-adrenal (HPA) axis in this condition (37). In the same cohort, Lappalainen et al (38) could also show that mean CAG repeat length of the androgen receptor (AR) gene is shorter in PA girls and that a polymorphic allele of the transcription factor TCF7L2, involved in the Wnt signalling pathway, was more frequent in PA subjects (39). However, genomewide association studies in appropriately powered cohorts of children with early androgen excess are currently lacking.…”
Section: Adrenarche Pubarche and Pubertymentioning
confidence: 86%
“…Postdigestion PCR products therefore represent methylated (inactive X chromosome) DNA sequence. PCR products were sized using 5% denaturing polyacrylamide gel electrophoresis in an ABI Prism 3730 DNA automated sequencer, and analyzed by using Genescan Analysis 3.1 software (Applied Biosystems) as described previously (28).…”
Section: Methodsmentioning
confidence: 99%
“…None of the 33 individual studies even approached such size, and this indicates the large collaborative efforts needed to confidently demonstrate, or refute, common genetic associations. Recent studies have also reported associations between shorter CAG repeat length and susceptibility to polycystic ovary syndrome in US adults [3] and premature adrenarche in Finnish children [4]. If confirmed, those findings would support the etiological role of increased androgen receptor activity in those conditions and therefore the rationale for androgen receptor blockade therapy.…”
Section: Ken K Ongmentioning
confidence: 80%